Selective detection of rutin in the presence of ascorbic acid with a carbon nanotube electrode. (12th December 2019) - Takahashi, Shota; Muguruma, Hitoshi; Osakabe, Naomi; Inoue, Hitoshi; Ohsawa, Tatsuya
Abstract: The selective electrochemical determination of rutin in the presence of ascorbic acid (AA) in food at the carbon nanotube (CNT) electrode is presented. The CNT electrode shows ideal characteristics for rutin detection, which are high and distinct response current towards a target, a small base current and high reproducibility/repeatability. In cyclic voltammetry, the prominent current peak that originated from catechol group oxidation in rutin is observed. The performance of the selective determination of rutin at the CNT electrode is in the concentration range of 0.024–4.0 mg ml −1 when the mass ratio of [AA]/[rutin] is up to 2.0.